Metallurgical and tribological aspects for squat formation in the aluminothermic weld HAZ edges of rails welded using aluminothermy. Issue 9 (24th July 2020) - Alves, Luiz Henrique Dias; Tepedino, Tiago Carvalho; Masoumi, Mohammad; Tressia, Gustavo; Goldenstein, Helio
Abstract : Purpose: The purpose of this paper is to present the results of a metallurgical, mechanical and tribological characterization of the weld and heat-affected zone (HAZ) of aluminothermic welding of premium rails used in heavy haul, looking into the origins of the squat defects associated with rail wear. Design/methodology/approach: A full factorial design of experiment was carried out for 24 welds of premium and super premium rails. The factors studied were chemical composition, welding gap and preheating time. The welds were inspected visually and by ultrasound to detect superficial and internal defects and characterized by macrographic analysis, hardness profile, tensile tests and microstructural characterization in scanning electronic microscopy. Pin-on-disk test were carried out to compare the tribological behavior of the different regions of the weld rail. Findings: Squat formation was shown to be associated with spheroidized pearlite regions formed on the HAZ of the welds, presenting near half the hardness of the weld metal. Thermal analysis showed that spheroidized pearlite is a result of partial austenitization at these positions. Tribological tests showed that low hardness regions presented smaller wear resistance than both the weld metal and the parent rail. Tensile test of the whole region resulted in brittle fracture along the weld metal. Originality/value: The results showed that it is essential to reduce the dimensions of the HAZ and the width of the hardness drop area to mitigate squat formation in the HAZ edges. Peer review: The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-01-2020-0020/